Semantic aspects of epistemic modality and the linguistic expression of reliability criterion - Turakulova, Dilafruz (The Lingua Spectrum, 2025)
As modern linguistics transitions from formal and substantial stages to an anthropocentric one, systematic approaches and contemporary methodological principles emphasize the necessity to describe linguistic units like grammatical modality and develop precise theoretical conclusions regarding their linguistic nature. Specifically, modality and closely associated evaluative aspects reflect the anthropocentric features of language, portraying the complex and continually changing human worldview. This article investigates the linguistic and semantic foundations, expression features, and relevance of epistemic modality as one of the subjective types of modality. The research highlights that the epistemic type of modality remains relatively underexplored, and its semantic essence lacks unanimous interpretation, thereby enhancing the topicality and scientific significance of this issue. Epistemic modality is analyzed as a linguistic category employed by humans to evaluate the reliability or uncertainty of events and phenomena. The primary aim of this article is to examine epistemic modality through the criterion of reliability, which expresses the speaker’s subjective attitudes toward statement content using semantic categories such as probability, certainty, and doubt